(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Background: Adherence and participant engagement are important determinants of the success of Adherence, Engagement and Participant Experiences in a Workplace Rajyoga Meditation Programme: Findings from an Eight-Week Intervention Study Among Corporate Executives workplace meditation interventions. Although meditation has been widely investigated for its psychological and organisational benefits, comparatively few studies have examined attendance, practice engagement and participant experiences during programme implementation. Understanding these process-related outcomes is essential for evaluating the feasibility and acceptability of workplace meditation interventions. Methods: This study was conducted as a secondary analysis of process-related outcomes from a larger experimental pre-test–post-test control group study among corporate executives working in the Environment, Health and Safety (EHS) function of a large agrochemical organisation in India. Ninety-four participants were randomly assigned to either a Rajyoga meditation group (n = 46) or an active control group receiving physical relaxation commentary (n = 48). Participants attended guided online sessions on weekdays for eight weeks. Attendance records, self-reported daily practice logs and participant feedback questionnaires were analysed using descriptive statistics. Results: Participants in the Rajyoga meditation group demonstrated higher attendance and engagement than those in the control group. Mean attendance was 64.95% in the Rajyoga group compared with 55.73% in the control group, while 60.9% and 31.3% of participants, respectively, met the predefined adherence criterion of attending at least 70% of sessions. Rajyoga participants also reported greater self-practice engagement, higher numbers of good-quality and distraction-free practice sessions, and more favourable feedback regarding emotional regulation, concentration, confidence in decision-making and overall programme benefit. Conclusion: The findings indicate that workplace Rajyoga meditation is a feasible and well-accepted intervention for corporate executives. Higher adherence, greater engagement and positive participant experiences suggest that Rajyoga meditation can be successfully integrated into organisational wellness programmes. Future research should investigate factors influencing long-term adherence and sustained practice across diverse workplace settings.